Emotional awareness amongst middle leadership. Issue 2 (10th June 2020) - Lambert, Steve
Abstract : Purpose: The purpose of this viewpoint paper is to explore middle leaders' ability to recognise emotions in the context of workplace research, and to propose measures that might support them in their role. Design/methodology/approach: This paper combines a contemporary literature review with reflections from practice to develop more nuanced understandings of middle leadership. This paper applied the Geneva Emotional Recognition Test (GERT) to explore the level of emotional recognition of 86 individuals (teachers to headteachers (equivalent to school principals)). Findings: The preliminary findings suggest that teachers and headteachers have higher levels of emotional recognition than middle and senior leaders. This paper subsequently argues that the task-orientated nature middle leadership compounds an individual's ability to engage effectively in relationship-orientated tasks. This explains why middle leaders scored lower on the GERT assessment. This is further inhibited by the anti-correlation in the brain's ability to deal with the task-positive network (TDM) and default mode network (DMN) processing functions where individuals operate in one neural mode for long periods. Research limitations/implications: The viewpoint paper proposes a number of implications for middle leaders and suggests that middle leaders should proactively seek out opportunities to be engaged in activities that support the DMN function of the brain and subsequently the relationship-orientated aspects of leadership, for example, coaching other staff members. However, it has to be recognised that the sample size is small and further work is needed before any generalisations can be made. Originality/value: This paper offers a contemporary review of the role of middle leaders underpinned by a preliminary study into individuals' ability to recognise emotions.